Behavior of DFIG Wind Turbine During Unbalanced Grid Voltage - Omer Elfaki; Wang Zezhong; Liu Qihui (Institute of Advanced Engineering and Science, 2014)
The use of doubly fed induction generators (DFIGs) in wind turbines has become quite common for the last few years. These machines provide variable speed and are driven with a power converter which is sized for a small percentage of the turbine-rated power. This paper presents a detailed model of an induction generator coupled to wind turbine system. Modeling and simulation of the induction machine using vector control computing technique is done. DFIG wind turbine is an integrated part of the distributed generation system, therefore, any abnormality’s associates with grid are going to affect the system performance considerably. Taking this into account, the performance of DFIG variable speed wind turbine under network fault is studied using simulation developed in MATLAB/SIMULINK.